Negative-bias temperature instability (NBTI) characterization of MOSFETS employing decoupled-plasma-nitrided gate oxides - Lai, Simon Chung Sing (2011)
The power-law time exponent n of negative-bias temperature instability (NBTI) is perceived to be able to explain the underlying physical mechanism. At present, molecular hydrogen is hypothesized as the diffusing specie, as it is able to reconcile the theoretical value of 0.167 with the experimentally obtained range of ~0.14-0.17. Recent findings revealed the presence of deep-level hole traps (DLHTs) near the Si bandgap, which may not have been discounted in earlier deductions of n. The purpose of this thesis is to establish correlations between those trap holes and measured time exponent, as well as to explore the change in oxide trap distribution away from the Si/SiO2 interface, during NBTI stress. The former was achieved by use of static and bipolar stress, together with charge pumping. This isolated the distortion DLHTs had on the time exponent values due to interface states. The latter was determined using an in-house flicker noise (1/f) measurement system. Results concluded that the presence of DLHTs led to an under-estimation of the time exponent values, to ~0.3-0.5, and the values were attributed to interfacial trapped charge above the Si mid-gap. In addition, these trapped charges exhibited both acceptor-like and donor-like behaviours, and may be related to E’ centres. 1/f noise data revealed that for thick gate devices, some neutral oxide traps were generated during NBTI.